Tetraploidy Enhances Boron-Excess Tolerance in Carrizo Citrange (Citrus sinensis L. Osb. × Poncirus trifoliata L. Raf.) - Ruiz, Marta; Quinones, Ana; Martínez-Alcántara, Belén; Aleza, Pablo; Morillon, Raphael; Navarro, Luis; Primo-Millo, Eduardo; Martínez-Cuenca, Mary-Rus (Frontiers Media, 2020)
Tetraploidy modifies root anatomy which may lead to differentiated capacity to uptake and transport mineral elements. This work provides insights into physiological and molecular characters involved in boron (B) toxicity responses in diploid (2x) and tetraploid (4x) plants of Carrizo citrange (Citrus sinensis L. Osb. Poncirus trifoliata L. Raf.), a widely used citrus rootstock. With B excess, 2x plants accumulated more B in leaves than 4x plants, which accounted for their higher B uptake and root-to-shoot transport rates. Ploidy did not modify the expression of membrane transporters NIP5 and BOR1 in roots. The cellular allocation of B excess differed between ploidy levels in the soluble fraction, which was lower in 4x leaves, while cell wall-linked B was similar in 2x and 4x genotypes. This correlates with the increased damage and stunted growth recorded in the 2x plants. The 4x roots were found to have fewer root tips, shorter specific root length, longer diameter, thicker exodermis and earlier tissue maturation in root tips, where the Casparian strip was detected at a shorter distance from the root apex than in the 2x roots. The results presented herein suggest that the root anatomical characters of the 4x plants play a key role in their lower B uptake capacity and root-to-shoot transport.